Use of innovation in marketing management of Slovak business enterprises - Lendel, Viliam; Varmus, Michal (Business: Theory and Practice, 2013)
The main aim of the paper is to create a model of the key elements affecting the use of innovation in marketing management on base of detailed analysis of literature and conducted research. This model should be supported by designed system how to work with innovations and knowledge of the business. The paper contains recommendations for the successful exploitation of innovation in marketing management as well as the proposed system. These recommendations should serve mainly to marketing managers like a valuable tool in the use of innovation in marketing management. The paper also identified areas of potential problems to those the managers have to focus on achieving a seamless work with innovations and knowledge of the business enterprise. The research used the following methods: comparative method, a method of qualitative evaluation, the structured and unstructured interviews, observation methods, analysis of documents (method of content analysis) and the questionnaire method.